Pengaruh Jenjang Pendidikan Terakhir Pemilik, Ukuran Usaha, Pengetahuan Akuntansi, dan Pengalaman Akuntansi Terhadap Dasar Pengambilan Keputusan Harga Jual Produk Usaha Mikro, Kecil, dan Menengah (UMKM) Pada Pasar Minggu Alun-Alun Kota Probolinggo. - Diesta Delliasty Dessyrias; R. Hery Koeshardjono; Khusnik Hudzafidah (Fakultas Ekonomi Universitas Panca Marga, 2018)
The purpose of this study was to determine the effect of the last owner's education level, business size, accounting knowledge, and accounting experience on the basis of decision making on the selling price of MSME products on the Sunday market in the Probolinggo Town Square. The population of this study is all MSME owners who sell at the Pasar Minggu Probolinggo Town Square every Sunday morning. Sampling uses a purposive sampling technique that is the selection of samples with certain criteria so that a sample of 32 companies is obtained. The method of data analysis uses multiple linear regression analysis. The results of the simultaneous testing showed that the independent variables (the owner's last education level, business size, accounting knowledge, and accounting experience) had an effect simultaneously (simultaneous) on the dependent variable (decision-making basis). And the partial test results state that the independent variables have a significant effect on the dependent variable Keywords: Last Education Level, Business Size, Accounting Knowledge, Accounting Experience, Use of Accounting Information, Micro, Small and Medium Enterprises (MSMEs)